Cloning, Developmental, and Tissue-Specific Expression of Sucrose:Sucrose 1-Fructosyl Transferase from Taraxacum officinale. Fructan Localization in Roots - Van den Ende, Wim (American Society of Plant Physiologists, 2000)
Sucrose:sucrose 1-fructosyl transferase (1-SST) is the key enzyme initiating fructan synthesis in Asteraceae. Using reverse transcriptase-PCR, we isolated the cDNA for 1-SST from Taraxacum officinale. The cDNA-derived amino acid sequence showed very high homology to other Asteracean 1-SSTs (Cichorium intybus 86%, Cynara scolymus 82%, Helianthus tuberosus 80%), but homology to 1-SST from Allium cepa (46%) and Aspergillus foetidus (18%) was much lower. Fructan concentrations, 1-SST activities, 1-SST protein, and mRNA concentrations were compared in different organs during vegetative and generative development of T. officinale plants. Expression of 1-SST was abundant in young roots but very low in leaves. 1-SST was also expressed at the flowering stages in roots, stalks, and receptacles. A good correlation was found between northern and western blots showing transcriptional regulation of 1-SST. At the pre-flowering stage, 1-SST mRNA concentrations and 1-SST activities were higher in the root phloem than in the xylem, resulting in the higher fructan concentrations in the phloem. Fructan localization studies indicated that fructan is preferentially stored in phloem parenchyma cells in the vicinity of the secondary sieve tube elements. However, inulin-like crystals occasionally appeared in xylem vessels.